P556 Surgery in high-risk paediatric Crohn's Disease treated with up-front anti-TNF agents and long-standing biologic therapy. (30th January 2023) - Musto, F; Distante, M; Dei Rossi, E; Calicchia, A; Veraldi, S; Mondi', F; Tarani, F; D'Arcangelo, G; Aloi, M
Abstract: Background: High-risk (HR) Crohn's Disease (CD) is associated with high surgical and progression rates. Therefore, recent ESPGHAN guidelines (GL) suggest starting an early anti-TNFα treatment to modify the natural history of the disease. The aim of our study was to evaluate the surgical rate in a population of HR-CD paediatric patients treated with up-front anti-TNFα agents and long-standing biologic therapy Methods: This is a retrospective, observational, single-center study conducted at the Paediatric Gastroenterology, Hepatology, and Endoscopy Unit at Policlinico Umberto I Hospital – Sapienza University of Rome. We collected data from all patients diagnosed with CD under 18 years, with a minimum follow-up of 12 months. between June 2008 to July 2022. Patients were then stratified at the diagnosis into HR and LR, based on ESPGHAN GL criteria. Demographic, clinical, laboratory, endoscopic, and imaging data were collected at 6, 12, 24, 36, 48, and 60 months Results: 130 patients were enrolled, 76 HR (58%) and 54 LR (42%) [median age 12.5 (IQR) yrs, female 45 (35%), medium follow-up 54±24 months]. The HR group included 39 patients (51%) with panenteric disease, 15 (20%) with a structuring behavior (B2), 3 (4%) with structuring/penetrating disease (B2-B3), and 26 (34%) with perianal involvement (p). Early anti-TNFα agents were started in 80% of patients <6 months from the diagnosis, while 15 (20%) started biological therapy between 6 and 12 months from the diagnosis. All patients continued biologic therapy throughout the study follow-up: 20 (26%) optimized anti-TNF, 25% switched biologic, 11% added an immunomodulator, and 4% combined 2 biological drugs. The surgical rate at 5 years was 29% (n=22) and 29% n=16) in HR and LR groups respectively (p-value 1, 0). Eleven % (n=8) of HR patients needed surgical resection, while perianal surgery (seton drainage, fistulotomy, fistulectomy) was performed in 18% (n=14), with no significant difference with LR group [(intestinal resection 18% (10/55), perianal surgery 11% (6/55), p > 0.05]. Perianal disease resulted positively associated with surgical risk (p 0.002, OR 5.62 CI 1.84-17.15) while small bowel imaging at the diagnosis was a protective factor for surgery (p 0.017, OR 0.23 CI 0.07-0.77). No significant difference was found in the interval free from surgery between HR and LR, although HR children mainly needed surgery in the first 12 months after the diagnosis. Conclusion: Our data suggest that paediatric patients with HR-CD treated with early anti-TNF agents and long-standing biologic therapy have a similar disease course and surgical risk to those with LR disease. At a 5-year follow-up, one-third of patients needed surgery, mainly in the first year after the diagnosis